Volumetric response quantified using T1 subtraction predicts long-term survival benefit from cabozantinib monotherapy in recurrent glioblastoma. Issue 10 (5th April 2018) - Ellingson, Benjamin M; Aftab, Dana T; Schwab, Gisela M; Hessel, Colin; Harris, Robert J; Woodworth, Davis C; Leu, Kevin; Chakhoyan, Ararat; Raymond, Catalina; Drappatz, Jan; de Groot, John; Prados, Michael D; et al.
Abstract: Background: To overcome challenges with traditional response assessment in anti-angiogenic agents, the current study uses T1 subtraction maps to quantify volumetric radiographic response in monotherapy with cabozantinib, an orally bioavailable tyrosine kinase inhibitor with activity against vascular endothelial growth factor receptor 2 (VEGFR2), hepatocyte growth factor receptor (MET), and AXL, in an open-label, phase II trial in patients with recurrent glioblastoma (GBM) (NCT00704288). Methods: A total of 108 patients with adequate imaging data and confirmed recurrent GBM were included in this retrospective study from a phase II multicenter trial of cabozantinib monotherapy (XL184-201) at either 100 mg ( N = 87) or 140 mg ( N = 21) per day. Contrast enhanced T1-weighted digital subtraction maps were used to define volume of contrast-enhancing tumor at baseline and subsequent follow-up time points. Volumetric radiographic response (>65% reduction in contrast-enhancing tumor volume from pretreatment baseline tumor volume sustained for more than 4 wk) was tested as an independent predictor of overall survival (OS). Results: Volumetric response rate for all therapeutic doses was 38.9% (41.4% and 28.6% for 100 mg and 140 mg doses, respectively). A log-linear association between baseline tumor volume and OS ( P = 0.0006) and a linear correlation between initial change in tumor volume and OS ( P = 0.0256) were observed. A significant difference in OS was observed between responders (median OS = 20.6 mo) and nonresponders (median OS = 8.0 mo) (hazard ratio [HR] = 0.3050, P < 0.0001). Multivariable analyses showed that continuous measures of baseline tumor volume (HR = 1.0233, P < 0.0001) and volumetric response (HR = 0.2240, P < 0.0001) were independent predictors of OS. Conclusions: T1 subtraction maps provide value in determining response in recurrent GBM treated with cabozantinib and correlated with survival benefit.